Evaluating the impact of tire stiffness on dynamic load in three-wheel trucks - Van Tong Em, Nguyen; Trong, Le Phan; Nguyen, Vo Thai (Sound & Vibration, 2026)
The dynamic loads that are produced by the various modes of transportation while they are in motion have a significant impact on the dynamic safety of the bridge or road, as well as the vehicle. Load impacts, which also cause structural damage to transportation infrastructure, are responsible for the catastrophic deterioration of the road and bridge system. In addition to this, it has an effect on the safety of drivers as well as the durability of the components of the vehicle. One of the characteristics that is connected to load is the stiffness of the tire. In this article, the structure of the multi-body system is separated, and the Newton-Euler equation is applied in order to develop the oscillation equation system for the vehicle. The ISO 8608:2016 standard is utilized in order to investigate the impact that varying levels of tire stiffness have on the dynamic load of three-axle vehicles that are driven on class B roads. The findings of the study indicate that the dynamic load on the tire increases in a manner that is proportional to the tire's stiffness at travel speeds. At 90 km/h on a class B road, increasing tire stiffness by 1.5 times raises dynamic load at the front axle from 50,389 N to 50,758 N (1.92%), while reducing stiffness by 0.5 times decreases load to 50,045 N (0.69%). Similarly, rear axle load rises from 46,874 N to 47,626 N (1.64%), indicating tire stiffness's quantitative impact on dynamic load.